The Keys to Managing Instruction and Behavior: Considering High Probability Practices. (May 2017) - Cooper, Justin T.; Scott, Terrance M.
Academics and behavior are inextricably linked, and as such, management of behavior should be considered not as an addition to the teacher's repertoire of skills but as an integral foundational component of effective instruction. Paradoxically, teachers report that students with challenging behavior are both their greatest challenge and that behavior management is the skill with which they are least prepared in their teacher preparation programs. In this article, the authors first review a rationale for considering high probability practices as those that provide the best probability for student success. Next, they present a set of key teacher-implemented management strategies as an essential part of the curriculum for any prospective teacher.